Chromaspirina guanabarensis sp. n. (Nematoda: Desmodoridae) and a new illustrated dichotomous key to Chromaspirina species - Maria, Tatiana Fabricio; Esteves, André Morgado; Smol, Nicole; Vanreusel, Ann; Decraemer, Wilfrida (Zootaxa, 2009)
A new species of Chromaspirina is described from Bica Beach, a polluted beach situated at Ilha do Governador, Guanabara Bay on the coast of Rio de Janeiro (Brazil). The new species belongs to the group of species within the genus which bears a poorly developed dorsal tooth. The new species is characterized by large body size, conoid tail shape, small acute dorsal tooth, long slender spicules with sclerotised hooked capitulum, and sexual dimorphism of the nonstriated part of the tail. A new illustrated dichotomous key to males of species of Chromaspirina is proposed.